Crop and forage production using saline waters - Kafi, M.; Khan, M. Ajmal (Delhi : Daya Pub. House, 2008)
Contributed papers presented at "International Workshop on Crop and Forage Production Using Saline Waters in Dry Areas" during May 7-10, 2006, organized jointly with the University of Birjand.
"Centre for Science & Technology of the Non-Aligned and Other Developing Countries."
Keywords: Forage plants -- Congresses; Saline irrigation -- Congresses